A study to assess self-medication practice among undergraduate medical students in a tertiary care hospital - Mani, Girija; Mokkaiyan, Pushpam; Rasheed, Razia Abdul (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Self-medication is an important public health concern globally. Many factors influence the practice of self-medication among medical students, because of the earlier professional exposure to information about drugs in their curriculum. In view of this, the present study has been designed to assess the practice of self- medication among undergraduate medical students. The objective of the study was to assess self- medication practice among undergraduates and to list out the commonly selected drugs and the conditions. Methods: This questionnaire based, cross- sectional model, was conducted among 150 students of 2nd year MBBS for a period of 3 months. This study was approved by Institutional Ethics Committee and written informed consent was obtained from all the participants. Results: Out of 150 students 71 were male and 79 were female students with an average age of 19.5±1.5. 80% of the candidates practiced self- medication, (48%) for headache, followed by cough and cold (45.83%). The drugs preferred primarily were analgesics (67%), antimicrobials (64%), and the source of information was previous prescription (80%). 70% of the study subjects felt that, no need to visit a doctor for minor illness, 50% of the students anticipated, fear of selecting wrong drugs and adverse effects. Conclusions: The practice of self- medication was highly prevalent among these future health care providers. Hence, this study emphasis an urgent need to strengthen the risk outweighs the benefit and consequences of self- medication practice.